A concise introduction to cultural anthropology - Sutton, Mark Q. (Routledge, an imprint of the Taylor & Francis Group, 2022)
"This book offers a concise and accessible overview of cultural anthropology for those coming to the subject for the first time. It introduces key areas of the discipline and touches on its historical developments and applied aspects. As well as traditional topics such as social organization, politics, and economics, the chapters engage with important contemporary issues including race, gender, sexuality, and colonialism. In a beginner friendly format, this book is ideal for students of Anthropology, as well as for the interested reader as an introduction to the subject"--Provided by publisher.